Collision between criminal law and custom in the crimes of child sexual abuse committed by the members of the native communities from the Amazon river basin - Cueva Zavaleta, Jorge (2007)
This present research is made from the necessity of leaving uncover the legal issue which is generated when criminal law of the majority mixed race culture is applied over the native communities from the Amazon River basin, colliding with their ancient customs which underlie their living style. Thus we propose decentralized legislation based on their own organisms to solve conflicts